Shale Heavy Metal Isotope Records of Low Environmental O2 Between Two Archean Oxidation Events - Ostrander, Chadlin M.; Kendall, Brian; Gordon, Gwyneth W.; Nielsen, Sune G.; Zheng, Wang; Anbar, Ariel D. (Frontiers in Earth Science, 2022)
Evidence of molecular oxygen (O2) accumulation at Earth’s surface during the Archean (4.0 to 2.5 billion years ago, or Ga) seems to increase in its abundance and compelling nature toward the end of the eon, during the runup to the Great Oxidation Event. Yet, many details of this late-Archean O2-story remain under-constrained, such as the extent, tempo, and location of O2 accumulation. Here, we present a detailed Fe, Tl, and U isotope study of shales from a continuous sedimentary sequence deposited between ~2.6 Ga and ~2.5 Ga and recovered from the Pilbara Craton of Western Australia (the Wittenoom and Mt. Sylvia formations preserved in drill core ABDP9). We find a progressive decrease in bulk-shale Fe isotope compositions moving up core (as low as 56Fe = –0.78 ± 0.08‰; 2SD) accompanied by invariant authigenic Tl isotope compositions (average 205TlA = –2.0 ± 0.6; 2SD) and bulk-shale U isotope compositions (average 238U = –0.30 ± 0.05‰; 2SD) that are both not appreciably different from crustal rocks or bulk silicate Earth. While there are multiple possible interpretations of the decreasing 56Fe values, many, to include the most compelling, invoke strictly anaerobic processes. The invariant and near-crustal 205TlA and 238U values point even more strongly to this interpretation, requiring reducing to only mildly oxidizing conditions over ten-million-year timescales in the late-Archean. For the atmosphere, our results permit either homogenous and low O2 partial pressures (between 10-6.3 and 10-6 present atmospheric level) or heterogeneous and spatially restricted O2 accumulation nearest the sites of O2 production. For the ocean, our results permit minimal penetration of O2 in marine sediments over large areas of the seafloor, at most sufficient for the burial of Fe oxide minerals but insufficient for the burial of Mn oxide minerals. The persistently low background O2 levels implied by our dataset between ~2.6 Ga and ~2.5 Ga contrast with the timeframes immediately before and after, where strong evidence is presented for transient Archean Oxidation Events. Viewed in this broader context, our data support the emerging narrative that Earth’s initial oxygenation was a dynamic process that unfolded in fits-and-starts over many hundreds-of-millions of years.